The banshees of Inisherin [videorecording (Blu-Ray)] - McDonagh, Martin; Farrell, Colin, 1976-; Gleeson, Brendan; Condon, Kerry, 1983-; Keoghan, Barry, 1992-; Davis, Ben, 1961-; Burwell, Carter (Searchlight Pictures, 2022)
Pádraic struggles to find normality and peace in his daily existence after his lifetime best friend, Colm, abruptly no longer wants to speak to him ever again. It's hard to avoid the consequences of that decision in a tiny Irish village, but as he searches for a reason he can accept and understand, the rest of his life seems to change around him as well, in some rather extreme and dire ways.